2012
DOI: 10.3996/052012-jfwm-038
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Trends of Freshwater Mussel Assemblages in the Meramec River Basin, Missouri, USA

Abstract: The Meramec River basin in eastcentral Missouri has one of the most diverse unionoid mussel faunas in the central United States with 40 species identified. Data were analyzed from historical surveys to test whether diversity and abundance of mussels in the Meramec River basin Big, Bourbeuse, and Meramec rivers, representing 400 river miles decreased between 1978 and 1997. We found that over 20y, species richness and diversity decreased significantly in the Bourbeuse and Meramec rivers but not in the Big River.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Hinck et al. () found declines in mussel density and attributed the declines to anthropogenic changes in the basin including the loss of riparian vegetation which, along with increased human population growth and the concomitant impacts, led to increased sedimentation, and thus changes in stream morphology leading to decreased habitat stability due to bedload movement. For the one location where mussel abundance remained similar, the authors stated that the exact reason that mussel abundance remained “robust” was unknown but may be due to the fact that despite anthropogenic impacts the geomorphology of this region (higher gradient and fewer pools) may have led to streambed stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hinck et al. () found declines in mussel density and attributed the declines to anthropogenic changes in the basin including the loss of riparian vegetation which, along with increased human population growth and the concomitant impacts, led to increased sedimentation, and thus changes in stream morphology leading to decreased habitat stability due to bedload movement. For the one location where mussel abundance remained similar, the authors stated that the exact reason that mussel abundance remained “robust” was unknown but may be due to the fact that despite anthropogenic impacts the geomorphology of this region (higher gradient and fewer pools) may have led to streambed stability.…”
Section: Discussionmentioning
confidence: 99%
“…Daniel and Brown (2013) also showed that the amount of agricultural lands in the corridor were negatively associated with mussel density and richness. Hinck et al (2012) found declines in mussel density and attributed the declines to anthropogenic changes in the basin including the loss of riparian vegetation which, along with increased human population growth and the concomitant impacts, led to increased sedimentation, and thus changes in stream morphology leading to decreased habitat stability due to bedload movement. For the one location where mussel abundance remained similar, the authors stated that the exact reason that mussel abundance remained "robust" was unknown but may be due to the fact that despite anthropogenic impacts the geomorphology of Lenz, Robertson, Fallon, and Ferrin (2003) examining phosphorus loading into the St. Croix found that storm events provided the largest instantaneous loading rates but that storm events affecting the tributaries in the lower portion of the basin resulted in loads and yields that were relatively small.…”
Section: Potential Mechanisms For These Changesmentioning
confidence: 99%
“…Our findings show the distribution of Medionidus walkeri has changed during the past century, with an overall reduction in range and fewer individuals found during recent surveys, displaying a common pattern observed for freshwater mussels across river systems worldwide (Cosgrove et al 2000, Geist & Kuehn 2005, Haag & Warren 2010, Hinck et al 2012, Jones et al 2014, Lopes-Lima et al 2016, Zipper et al 2016. The observed spatiotemporal changes in distribution appear confined to the periphery of the species' range in the lower Withlacoochee, lower Su wannee, and upper Santa Fe subbasins (Fig.…”
Section: Surveys and Distributionmentioning
confidence: 84%
“…Mussel distribution and diversity in the Meramec River basin declined between 1979 and 1997, and a series of threats were implicated; these included excessive sedimentation, altered hydrology and geomorphology, altered riparian condition, and water quality contaminants (Hinck et al 2012). More specific and spatially explicit identification of threats requires a local knowledge of drivers that have changed in the system.…”
Section: Box 3 Identification Of Threats To the Meramec River Mussel mentioning
confidence: 99%